2020
DOI: 10.3390/cells9102282
|View full text |Cite
|
Sign up to set email alerts
|

LPS-Induced Endotoxemia Evokes Epigenetic Alterations in Mitochondrial DNA That Impacts Inflammatory Response

Abstract: Mitochondrial DNA (mtDNA) plays a vital role as a damage-associated molecular pattern in sepsis being able to shape the immune response. Since pathogen recognition receptors of innate immune cells are activated by demethylated DNA only, we set out to investigate the amount of DNA methyltransferase 1 (DNMT1) in mitochondria and the extent of mtDNA methylation in a human endotoxin model. Peripheral blood mononuclear cells of 20 healthy individuals were isolated from whole blood and stimulated with lipopolysaccha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 25 publications
0
13
0
Order By: Relevance
“…Global 5-mC and 5-hmC mtDNA content Global hypomethylation of mtDNA in fructose-fed rats as well as higher mtDNA content and transcription of several mtDNA genes [116] It has been reported that mtDNA methylation is modulated by exposure to particulate matter (PM 1 and PM 2.5 ), air benzene, traffic-derived elemental carbon [56,108,113], particle-containing welding fumes [120], endocrine disruptors [109], maternal smoking [112,118,129], chrome [117], arsenic [59] and iron [121], as well as to the pharmacological agent valproic acid [51], to the demethylating agents 5-azacytidine and vitamin C [70,122] and to HIV infection and cocaine [125]. Variations in mtDNA methylation patterns have also been associated with various endogenous metabolites, including thyroid hormones [119], homocysteine [114,126], betaine [110], glucose [79,80], L-carnitine [124], lipopolysaccharides [127] and mitochondrial-derived peptides [123]. Moreover, nutrients from the diet, including lipids and fructose, were also able to modulate mtDNA methylation levels in animal models [111,115,116].…”
Section: Enzyme-linked Immunosorbent Assaymentioning
confidence: 99%
See 1 more Smart Citation
“…Global 5-mC and 5-hmC mtDNA content Global hypomethylation of mtDNA in fructose-fed rats as well as higher mtDNA content and transcription of several mtDNA genes [116] It has been reported that mtDNA methylation is modulated by exposure to particulate matter (PM 1 and PM 2.5 ), air benzene, traffic-derived elemental carbon [56,108,113], particle-containing welding fumes [120], endocrine disruptors [109], maternal smoking [112,118,129], chrome [117], arsenic [59] and iron [121], as well as to the pharmacological agent valproic acid [51], to the demethylating agents 5-azacytidine and vitamin C [70,122] and to HIV infection and cocaine [125]. Variations in mtDNA methylation patterns have also been associated with various endogenous metabolites, including thyroid hormones [119], homocysteine [114,126], betaine [110], glucose [79,80], L-carnitine [124], lipopolysaccharides [127] and mitochondrial-derived peptides [123]. Moreover, nutrients from the diet, including lipids and fructose, were also able to modulate mtDNA methylation levels in animal models [111,115,116].…”
Section: Enzyme-linked Immunosorbent Assaymentioning
confidence: 99%
“…However, several other studies that have carefully followed the necessary precautions for the study of mtDNA methylation, or that used techniques for which bisulfite treatment was not necessary, successfully identified the presence of methylation in the mitochondrial genome [ 61 , 73 , 84 , 110 , 127 , 137 ]. For example, Patil and co-workers performed a whole-genome bisulfite sequencing after linearization of mtDNA, finding a higher degree and frequency of methylation, particularly in the L-strand when compared to the H-strand in various human cell cultures [ 61 ].…”
Section: Debate On the Existence And Function Of Mtdna Methylationmentioning
confidence: 99%
“…In specific, we demonstrate that IL-1β reduces SDHB expression through DNMT1-dependent DNA methylation of the SDHB promoter. Several studies have shown that inflammation promotes DNA methylation and thereby regulates gene expression [6266]. Particularly IL-1β was demonstrated to increase DNA methylation in different genes in a cell type-specific manner [63,67].…”
Section: Discussionmentioning
confidence: 99%
“…It should be noted that the studies shown in Figure 5 employed bisulfite conversion to determine the methylation level, and in the present study, we used a technique without this conversion because it was previously reported that incomplete bisulfite conversion can introduce artifacts [53]; however, despite the different techniques used to assess the level of methylation, hypomethylation was found to exist only in subjects with cigarette consumption.…”
Section: Discussionmentioning
confidence: 99%